2019
DOI: 10.5539/gjhs.v11n9p93
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Knowledge and Attitudes on Established Breastmilk Bank in Limpopo Province, South Africa

Abstract: BACKGROUND: Breastfeeding is recommended as the best practice which results in normal growth and development of the healthy infants.  In cases where the mother is unable to provide adequate breastmilk due to unavoidable circumstances, pasteurised donated breastmilk from the bank should be considered for hospitalized or preterm babies. OBJECTIVES: To explore and describe women’s knowledge and attitudes related to established breastmilk bank in Mankweng area. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…After it was explained to them, they appreciated the idea and its advantages for babies when their mother's milk is not available. This finding is similar to what has been reported in a study among women in Mankweng hospital in Limpopo Province, South Africa, where mothers who were admitted were the only ones who were aware of the DHMB compared to mothers who were attending antenatal clinics (Mantji et al, 2019 ). This finding was contrary to the study that was conducted in North West Province in South Africa, where participants heard about DHMB from facilities before delivery (Lubbe et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After it was explained to them, they appreciated the idea and its advantages for babies when their mother's milk is not available. This finding is similar to what has been reported in a study among women in Mankweng hospital in Limpopo Province, South Africa, where mothers who were admitted were the only ones who were aware of the DHMB compared to mothers who were attending antenatal clinics (Mantji et al, 2019 ). This finding was contrary to the study that was conducted in North West Province in South Africa, where participants heard about DHMB from facilities before delivery (Lubbe et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Participants valued donor milk as it assists them in their babies' growth, and they viewed it as a beneficial temporary solution for insufficient milk. This finding was contrary to a study that was conducted in Limpopo Province, South Africa, where mothers had a different view that they were not comfortable accepting donated breast milk for their children (Mantji et al, 2019).…”
Section: Willingness To Use Donor Human Breast Milkcontrasting
confidence: 99%
“…It has been shown to provide health benefits for all new-born infants including ones at high risk or with very low birth weights [ 2 ]. In the absence of the infant’s mother due to maternal illness, death, medication, disability, insufficient milk production, allergies, or prematurity, donated breastmilk from the breastmilk bank can become the ideal option [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Indonesia indicated low acceptability of DBM among healthcare workers and most mothers due to the fear of transmission of diseases from the donated milk [ 20 ]. In SA (Limpopo, Northwest and Kwazulu Natal provinces), healthcare workers were concerned about the safety of donated milk, particularly regarding HIV transmission and transportation of donated milk from the donor to the bank, which might affect the quality of the milk [ 4 , 21 , 22 , 23 ]. These concerns were only reported amongst breastfeeding women receiving healthcare services at Mankweng hospital and clinic [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation